Bacteroides fragilis sacral spondylodiscitis and epidural abscess after sacrocolpopexy: a case report and literature review. Issue 9 (September 2019) - Miksić, Nina Gorišek; Kljaić Dujić, Milka; Rejc Marko, Jana; Voršič, Matjaž; But, Igor
Spondylodiscitis with or without epidural abscess is a rare, although serious, complication after sacrocolpopexy. We present a case of an 81-year-old patient who developed anaerobic Bacteroides fragilis sacral spondylodiscitis with epidural abscess 18 weeks after laparoscopic sacrocolpopexy. Because of the patient's old age, comorbidities, and further complications during hospitalization, she was treated conservatively with an early switch to oral antimicrobial therapy with good oral bioavailability. Because of retention of titanium bone anchors in the first sacral vertebra, oral antimicrobial treatment with biofilm-active clindamycin was prolonged to 6 months. This conservative approach was successful. One year after discontinuation of antimicrobial therapy, the patient had no signs of recurrence of infection or other complications. With retention of implanted material, we preserved good pelvic support with a good effect on the patient's quality of life. A combined surgical and antimicrobial therapy with mesh removal is the treatment of choice in most cases of spinal infectious complications. However, we would like to emphasize the need for an individualized therapeutic approach in the growing population of frail and polymorbid, older patients, where a conservative approach can have important effects on the quality of life. Infectious complications can have devastating consequences in these patients.